1985
DOI: 10.1002/jnr.490140202
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and growth factors induce the synthesis of glial fibrillary acidic protein in rat brain astrocytes

Abstract: Glial fibrillary acidic protein (GFAP) is the major constituent of glial filaments and is restricted within the CNS to astrocytes. As with other classes of intermediate filament proteins, the regulation of GFAP expression is poorly understood. Utilizing highly purified cultures of astrocytes and a chemically defined (CD) medium, we have demonstrated that the expression of GFAP is subject to regulation by hormones and growth factors. The concentration of GFAP/mg protein was induced 2-4-fold in the presence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(81 citation statements)
references
References 28 publications
7
74
0
Order By: Relevance
“…Reports have indicated that bFGF induces morpholo gical changes in astrocyte cells both in vitro and in vivo (14,28). In this study, staining with anti-GFAP anti body showed stronger gliosis in the grafted regions in the 50 ng bFGF-treated group as compared with the control and 5 ng bFGF-treated rats (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Reports have indicated that bFGF induces morpholo gical changes in astrocyte cells both in vitro and in vivo (14,28). In this study, staining with anti-GFAP anti body showed stronger gliosis in the grafted regions in the 50 ng bFGF-treated group as compared with the control and 5 ng bFGF-treated rats (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Although the relation between induction of gliosis and improve ment of neuronal survival has not been clarified exact ly, the dense gliosis induced by a high dose of bFGF (50 ng) presumably results in less grafted neuron survi val and less amelioration of abnormal rotations. Besides the morphological alteration of glial cells, bFGF induced other responses in glial cells, such as proliferation (29), glial fibrillary protein synthesis (28), nerve growth factor release (30), glutamine synthase synthesis (31) and protein kinase activation (32). Among these bFGF-induced multiple responses, there may be an ability to stimulate dopaminergic neurons, e.g., by release of a dopaminotrophic factor, but this effect has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The same tendency was observed for PGE 2 levels, although it did not reach statistical significance. Prostaglandins have been shown to have numerous effect on astrocytes in vitro including upregulating GFAP expression [31]. Thus, it should be further clarified if the astrocytic activation observed during aging is either the consequence or the cause of altered AA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence also suggests that glia serve as targets for these hormones. For example, glucocorticoids can induce glycerol phosphate dehydrogenase and glutamine synthetase activity (12,18,33,(47)(48)(49), change cell shape and microfilament contents (50,51) and suppress cell growth (52). Since glucocorticoids such as CORT and DEX also bind to mineralocorticoid Type I receptors with high affinity (24), questions concerning which type of receptor mediates glucocorticoid-induced responses on specific cell types are difficult to study in vivo.…”
Section: Discussionmentioning
confidence: 99%